Needs Analysis of Innovative Chemistry Teaching Materials Integrated with Ethnopedagogy Oriented to 21st Century Learning - Siswanto, Siswanto; Tarigan, Anjany Tasya Surabika; Silaban, Ramlan; Situmorang, Manihar (Jurnal Inovasi Pembelajaran Kimia, 2025)
21st-century education emphasizes six core competencies: critical thinking, creativity, collaboration, communication, character, and citizenship. However, the PISA 2022 results indicate that Indonesia’s performance remains relatively low, highlighting the need for improvement in developing students’ essential skills. This study aims to analyze the needs for innovative chemistry teaching materials that are integrated with ethnopedagogy and oriented toward 21st-century learning as an effort to enhance students’ 21st-century competencies. This research employed a descriptive qualitative approach conducted at SMP Negeri 1 Sei Bingai, Langkat Regency, using interviews, observations, and document analysis. The data were analyzed through four stages: data collection, data reduction, data presentation, and conclusion drawing. The results showed that the current science textbooks do not adequately support the development of 21st-century skills, and teachers reported that students’ competencies in this area remain low. All science teachers expressed the need for teaching materials integrated with ethnopedagogical. Furthermore, 74% of students indicated a need for innovative learning materials, 90% desired the integration of ethnopedagogy, and 94% supported the implementation of 21st-century learning approaches. These findings highlight the need for innovative, contextual, and culturally based chemistry materials to enhance students’ 21st-century skills and learning experiences.